alec_tronn
New member
- Joined
- Feb 3, 2008
- Messages
- 1
Show that (kn)! is divisible by (n!)^k.
My attempts at a solution:
In my first attempt, I tried a factorization of the problem as follows:
(kn)! = (kn)*(kn-1)*(k-2)...(kn-n+1) *
((k-1)n)*((k-1)n-1)*((k-1)n-2)*((k-1)n-1)...((kn-1)n-n+1)*
((k-2)n)*((k-2)n-1)*((k-2)n-2)*((k-2)n-1)...((kn-2)n-n+1)*
.
.
.
((k-k+1)n)*((k-k+1)n-1)*((k-k+1)n-2)*((k-k+1)n-1)...((k-k+1)n-n+1)
Then, I wanted to factor that into: (k!)(n!)^k... which I now realize is illegal.
Then, I wanted to do induction, so I tried to do the first couple k's, so that I'd have a base case to start from:
k=1, (kn)! = (1n)! which is obviously divisible by (n!)^1
k=2, (kn)! = (2n)! = (2n)(2n-1)(2n-2)(2n-3)(2n-4)(2n-5)(2n-6)(2n-7)(2n-8).....
= 2(n)(2n-1)2(n-1)(2n-3)2(n-2)(2n-5)2(n-3)(2n-7)2(n-4).....
= (2^n)(n!)(2n-1)(2n-3)(2n-5)(2n-7)...
I feel like I found a pattern... if I can find another n! in this, maybe I can generalize and all would be good and well?
Does anybody have any advice? Thanks for any help you can give me!
My attempts at a solution:
In my first attempt, I tried a factorization of the problem as follows:
(kn)! = (kn)*(kn-1)*(k-2)...(kn-n+1) *
((k-1)n)*((k-1)n-1)*((k-1)n-2)*((k-1)n-1)...((kn-1)n-n+1)*
((k-2)n)*((k-2)n-1)*((k-2)n-2)*((k-2)n-1)...((kn-2)n-n+1)*
.
.
.
((k-k+1)n)*((k-k+1)n-1)*((k-k+1)n-2)*((k-k+1)n-1)...((k-k+1)n-n+1)
Then, I wanted to factor that into: (k!)(n!)^k... which I now realize is illegal.
Then, I wanted to do induction, so I tried to do the first couple k's, so that I'd have a base case to start from:
k=1, (kn)! = (1n)! which is obviously divisible by (n!)^1
k=2, (kn)! = (2n)! = (2n)(2n-1)(2n-2)(2n-3)(2n-4)(2n-5)(2n-6)(2n-7)(2n-8).....
= 2(n)(2n-1)2(n-1)(2n-3)2(n-2)(2n-5)2(n-3)(2n-7)2(n-4).....
= (2^n)(n!)(2n-1)(2n-3)(2n-5)(2n-7)...
I feel like I found a pattern... if I can find another n! in this, maybe I can generalize and all would be good and well?
Does anybody have any advice? Thanks for any help you can give me!